Design and implementation of warehouse management improvement strategy using barcode system approch at PT Latinusa Tbk - Frusman, Pengky; Wibisono, Dermawan (2014)
The availability of good warehouse management is one of important aspect should be concerned in a company, especially for a company which engaged in manufacturing.The basic activities that are managed by warehouse management includes receiving goods from production section, transferring them from one location to another within same warehouse or another, delivering to customers include picking and loading activities, and physical verification activities compare to the recorded data in the system.PT Latinusa Tbk as the only one company in Indonesia that produces tinplate, raw material for cans, faced several warehouse problems, such as missed products shipping to customers, long time execution to look for goods in warehouse due to position of goods were not updated, any changes in goods’ specifications were not followed by reattachment process of goods’ tickets, inaccurate data recording, and update of goods position was not carried out regularly. This evidence consequently decreasing low warehouse management image in which it will give effect on customers’ trust for the company.This paper proposed a suggestion to PT Latinusa Tbk to improve quality of warehouse management system for implementing information technology approach namely Barcode System.The proposed solution includes: 1. Design of process warehouse management activities involve stock management, record keeping, delivery activity to customers, 2. Design of barcode format that will be used through optimization of feature from two-dimensional barcode format, 3. Design of systems to increase barcode solution with existing ERP System with necessity of estimated costs from implementation and proposed implementation time schedule.To provide additional insight relates to integrated barcode system solutions for the warehouse, it conducted a comparation in performances of implemented integrated barcode system in PT Frisian Flag and PT Krakatau Steel Tbk.Research shows that implementation of barcode solution can affect positively the quality of the warehouse management both in terms of time savings, loss of income due to customers’ claims, data quality in system, personnel’s cost, as well as company image in providing high quality delivery services to customers.